Oral manifestations and dental considerations of hereditary haemorrhagic telangiectasia in paediatric population — a systematic review - V. Vanmathi; K. Shunmugavelu; A. Shanmugam; S. Srikanthan; G. R. Vadakkettath; B. E. Rao (Аллергология и Иммунология в Педиатрии, 2024)
.